2013
DOI: 10.1188/13.cjon.17-03ap
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction With Breast and Colorectal Cancer Survivorship Care Plans

Abstract: Cancer survivors face several challenges following the completion of active treatment, including uncertainty about late effects of treatment and confusion about coordination of follow-up care. The authors evaluated patient satisfaction with personalized survivorship care plans designed to clarify those issues. The authors enrolled 48 patients with breast cancer and 10 patients with colorectal cancer who had completed treatment in the previous two months from an urban academic medical center and a rural communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 21 publications
1
49
0
1
Order By: Relevance
“…Cancer survivors agreed, when asked, that TS/SCPs were useful and effective, particularly for written documentation of treatment [22,34,35,38,39,41,42,[51][52][53], while survivors' preferences reported in Faul et al indicated that the provision of the TS/SCP reduced worry [38]. Two studies did not show an overwhelming survivor preference of web-based/electronic TS/SCP over a printed paper copy [39,43]; however, Mayer et al indicated survivor preference for a face-to-face consultation [43].…”
Section: Cancer Survivor Scp Preferencesmentioning
confidence: 92%
See 1 more Smart Citation
“…Cancer survivors agreed, when asked, that TS/SCPs were useful and effective, particularly for written documentation of treatment [22,34,35,38,39,41,42,[51][52][53], while survivors' preferences reported in Faul et al indicated that the provision of the TS/SCP reduced worry [38]. Two studies did not show an overwhelming survivor preference of web-based/electronic TS/SCP over a printed paper copy [39,43]; however, Mayer et al indicated survivor preference for a face-to-face consultation [43].…”
Section: Cancer Survivor Scp Preferencesmentioning
confidence: 92%
“…Thirteen studies (45 %) utilized a known TS/SCP template in the methodological design. The ASCO template (n=5) was the most commonly used [31,35,37,38,44] followed by LIVESTRONG TM [40,43] and Journey Forward [21,51]. Mayer et al [43] queried participants on their preferences of four TS/SCP templates (ASCO, Journey Forward, LIVE STRONG TM , and the South Atlantic Division of American Cancer Society SCP).…”
Section: Clinical Use Of Ts/scpsmentioning
confidence: 99%
“…The ISCP meets these needs for information and improves knowledge of the illness and treatments (Curcio et al, 2012;Faul et al, 2012). According to Sprague et al (2013), survivors are satisfied with the ISCP and find it to be useful and to facilitate an understanding of their diagnoses, treatments, follow-up, and the recommended health-promoting behaviour. Feeling informed would seem to help in planning changes in behaviour and foster responsibility for one's health (Hill-Kayser et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The ongoing discussion in the scientific community about the role of primary care in the follow-up of cancer patients and the need to define a clinical pathway, clarify the follow-up objectives, and identify a discharge cut-off from hospital to primary care, as well as a higher focus on survivorship are considered essential pillars [25][26][27]. The moment of discharge is considered critical and is aligned with cancer survivors' concerns about the format and content of the information shared at the moment of discharge from hospital, among others [28][29][30].…”
Section: Discussionmentioning
confidence: 99%